PERPUSTAKAAN DAN GERAKAN SADAR LITERASI SEBAGAI UPAYA MENANGKAL HOAKS - Fitriani, Susialia (UIN Raden Intan Lampung, 2020)
The explosion of information has become a characteristic of the world today, information has become an unavoidable entity. Therefore, intelligence in choosing good and correct information is an appropriate step in warding off the hoax. Hoax is news or information that contains elements of lying, spread quickly and has a negative impact on the democratic order. The library as a legitimate provider of information should have taken part in counteracting hoax attacks in order to create an intelligent and civilized society, the society that is thinking clearly and not easily provoked by false news. One effort that can be taken by the library as an information provider is to actively promote literacy awareness in all levels of society, starting from the school community and the wider society in general. With information literacy, someone will be able to process information appropriately. Information literacy is an absolute competency that must be possessed by every member of society, especially in the digital era, which every second produces countless amounts of information, so being smart and critical of information is a surefire strategy in the fight against the hoax.